2021
DOI: 10.1101/2021.03.14.435220
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discovery of viral myosin genes with complex evolutionary history within plankton

Abstract: Nucleocytoplasmic large DNA viruses (NCLDVs) infect diverse eukaryotes and form a group of viruses with capsids encapsulating large genomes. Recent studies are increasingly revealing a spectacular array of functions encoded in their genomes, including genes for energy metabolisms, nutrient uptake, as well as cytoskeleton. Here, we report the discovery of genes homologous to myosins, the major eukaryotic motor proteins previously unrecognized in the virosphere, in environmental genomes of NCLDVs from the surfac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Viral rhodopsins may permit viruses to modify host phototaxis during infection, which may promote their proliferation (Gallot-Lavallée and Archibald, 2020). Proteins involved in cytoskeletal dynamics have also been found to be quite common in a variety of marine giant viruses; viral homologs to actin, myosin, and kinesin genes could potentially benefit viruses by manipulating the host's cytoskeleton by using host motor proteins to traffic virions or maintain the localization of viral machinery during infection (Ha et al, 2021;Kijima et al, 2021;Da Cunha et al, 2022). These recent findings collectively suggest that giant viruses use a broad assortment of functional genes to manipulate host physiology and alter the intracellular environment to promote virion propagation.…”
Section: Introductionmentioning
confidence: 99%
“…Viral rhodopsins may permit viruses to modify host phototaxis during infection, which may promote their proliferation (Gallot-Lavallée and Archibald, 2020). Proteins involved in cytoskeletal dynamics have also been found to be quite common in a variety of marine giant viruses; viral homologs to actin, myosin, and kinesin genes could potentially benefit viruses by manipulating the host's cytoskeleton by using host motor proteins to traffic virions or maintain the localization of viral machinery during infection (Ha et al, 2021;Kijima et al, 2021;Da Cunha et al, 2022). These recent findings collectively suggest that giant viruses use a broad assortment of functional genes to manipulate host physiology and alter the intracellular environment to promote virion propagation.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, we also found several transcripts matching to predicted cytoskeletal proteins, including actin, myosin, and kinesin. Recent studies have identified divergent actin, myosin, and kinesin homologs in Nucleocytoviricota and, in some cases, it has been suggested they may have played a role in the emergence of this protein in extant eukaryotic lineages ( 65 67 ). We found three expressed viral genes with predicted myosin motor domains and one with kinesin domains, and subsequent analysis of all Nucleocytoviricota genomes in our reference database recovered an additional 109 myosin and 200 kinesin homologs.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the authors present data confirming the expression of several transcripts related to cytoskeletal proteins, including actin, myosin, and kinesin. Remarkably, previous studies have identified cytoskeletal-related homologs in Nucleocytoviricota genomes ( 18 20 ). Ha and colleagues contributed to this knowledge by presenting 109 myosin and 200 kinesin homologs.…”
Section: Commentarymentioning
confidence: 99%